Empowerment of Socio-Economic Institutions in Religious Tourism Villages Based on Local Wisdom - Chusmeru, Chusmeru; Sulaiman, Adhi Iman; Adi, Tri Nugroho; Runtiko, Agus Ganjar; Rofik, Ahmad; Weningsih, Sri (Rescollacom (Research Collaborations Community), 2023)
The research aims to analyse and design a socio-economic institutional empowerment programme in a unique and attractive religious tourism village based on local wisdom. The study used the Participatory Action Research (PAR) method in a tourist village that is unique as a religious and natural tourism destination in Banyumas Regency, Central Java Province, Indonesia. Data collection through dialogue, observation, documentation, and focus group discussions. Data was analyzed in a participatory, and research informants were determined by purposive sampling of stakeholders in the tourism village. The research results showed that potential of the tourism village is very large and has met the criteria of something to see in the form of flowing rivers as well as beautiful and natural hills, something to do with ritual events as a religious destination, and something to buy, namely food and beverage products that are distinctive, unique and interesting. Reference for further studies using a constructivist paradigm through deeper ethnographic and symbolic interaction research methods. Practical implications can be used as a location for community service, practicum, internships, practical work, and real work lectures for students and lecturers on the development of religious tourism villages and productive tourism villages. Research novelty namely construct a religious tourism village that has distinctive, unique, and interesting characteristics and previously and empowerment programs for the development of socio-economic institutions for local communities. The hope is that it can become a recommendation for the formulation of public and social policies to develop a religious tourism village based on local wisdom.